2015
DOI: 10.1007/s00280-015-2737-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of intraperitoneal nanoparticulate paclitaxel (Nanotax®) in patients with peritoneal malignancies

Abstract: Purpose This multicenter, open-label, dose-escalating, phase I study evaluated the safety, tolerability, pharmacokinetics and preliminary tumor response of a nanoparticulate formulation of paclitaxel (Nanotax®) administered intraperitoneally for multiple treatment cycles in patients with solid tumors predominantly confined to the peritoneal cavity for whom no other curative systemic therapy treatment options were available. Methods Twenty-one patients with peritoneal malignancies received Nanotax® in a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
(35 reference statements)
0
39
0
Order By: Relevance
“…Compared to free drugs, IP-administered nanoformulated cancer drugs may have favorable pharmacokinetic and biodistribution profiles [45], and at least 2 nano-therapeutics, Abraxane™ and Nanotax™ are being clinically evaluated in PC clinical trials [46,47]. Our study was designed to evaluate the effect of functionalizing NPs with the p32-binding linTT1 peptide on the tumor targeting and antitumor efficacies of drug-loaded NPs upon IP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to free drugs, IP-administered nanoformulated cancer drugs may have favorable pharmacokinetic and biodistribution profiles [45], and at least 2 nano-therapeutics, Abraxane™ and Nanotax™ are being clinically evaluated in PC clinical trials [46,47]. Our study was designed to evaluate the effect of functionalizing NPs with the p32-binding linTT1 peptide on the tumor targeting and antitumor efficacies of drug-loaded NPs upon IP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Their recent Phase I clinical trial demonstrated that IP administration of Nanotax ® particles provides higher and prolonged peritoneal paclitaxel levels with minimal systemic exposure and reduced toxicity compared to IV paclitaxel administration. 9 IP therapy has not been widely accepted despite the positive clinical results, due to catheter-related complications, the high rate of grade 3/4 toxicities and the poor tolerance of the regimen. An implantable, nonresorbable IP micro-device was developed to release a chemotherapeutic agent to the peritoneal cavity at a constant rate.…”
mentioning
confidence: 99%
“…administration of chemotherapeutics has obvious advantages in pharmacokinetics, which could elevate the local drug concentration about 450-2900 times compared to systemic chemotherapy (17). A previous report indicated that nanoparticles could target the lymphatic system and act as slow-release formulations after i.p.…”
Section: In Vivo Pharmacokinetic Studymentioning
confidence: 99%